اختلاف الأصوليين في قاعدة (العبرة بما رواه الراوي لا برأيه) وأثره في فقه المناكحات - Azis Faturokhman (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2021)
This study aimed to discuss kaidah AL-ʻIBROTU BIMÂ ROWÂHU AL-RÂWI LÂ BIRAʼYIH and explained the dissent of ushuliyyin on that kaidah then applied it to the context of fiqh munakahat. Based on the results of the study, the author concluded that the rajih opinion was jumhur ulama opinion, which said that the hadith excluded by the rawi was a hujjah. As for the opinion of the ulama hanafi, if the rawi opinion was different from the hadith that he narrated, then the hadith could not be used as hujjah and it became a weak opinion according to the arguments and the discussions that had been elaborated by the author in his study.